The impact of social media influencers on purchase intention towards beauty products in Malaysia - Abu Talib, Siti Nurul Ain (2022)
Due to advancements in technology and social media, the popularity of social media influencers has grown, and more businesses and advertisers are utilizing them to enhance revenue and sales. This study aims to add to this field of study by examining the impact of social media influencers on the purchase intention of beauty products and by gaining a better knowledge of which characteristics significantly impact buy intention in Malaysia. Based on the literature review, a framework was developed that emphasized the features of social media influencers that have the potential to affect the purchase intent of beauty goods. A quantitative study employing a self-administered questionnaire with 269 participants examined the framework hypothesis. This study has four predictors: trustworthiness, expertise, likability, and similarity. The findings indicate that all four characteristics significantly influence Malaysia's propensity to purchase beauty products. The data revealed that likeability and expertise have a more decisive influence on consumer purchase intent than trustworthiness and similarity after analysing the data with version 28 of the Statistical Package for Social Science (SPSS) software. This study contributed new insights to our present understanding of the significant components of social influencer participation. With the help of these contributions, managers can consciously choose the characteristics to look for in social media influencers.